Determining the most suitable spectral range for TDLS – a quantitative approach. (August 2022) - Bahr, Marc-Simon; Baumann, Bernd; Wolff, Marcus
Highlights: Mathematical algorithm to determine optimal center wavelength for laser spectroscopy. Applicable to all tunable semiconductor lasers. Requires only theoretical spectra, e. g. from a known database. Detailed description of the determination process. Abstract: We present a mathematical method which allows determination of an optimal spectral range for gas mixture analysis based on theoretical absorption spectra. The resulting center wavelength is particularly suited for tunable diode laser spectroscopy (TDLS). The procedure contains several steps of numerical calculations which can easily be implemented in almost any programming language. We apply our method to three exemplary mixtures of hydrocarbons and present and validate the individual results.